Waiting List Dynamics and Lung Transplantation Outcomes After Introduction of the Lung Allocation Score in The Netherlands. Issue 10 (7th September 2021) - Hoffman, Thijs W.; Hemke, Aline C.; Zanen, Pieter; Luijk, Bart; Hoek, Rogier A.S.; Verschuuren, Erik A.M.; van Kessel, Diana A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The Netherlands was the third country to adopt the lung allocation score (LAS) for national allocation of donor lungs in April 2014. Evaluations of the introduction of the LAS in the United States and Germany showed mainly beneficial effects, including increased survival after transplantation. Methods: Data for transplant candidates from 2010 to 2019 were retrieved from the Dutch Transplant Foundation database. Diagnosis categories and outcomes were compared between the periods before and after the introduction of the LAS. Time-dependent Cox regression and Fine-Gray analyses were performed to compare the chance for transplantation before and after introduction of the LAS. Results: The cohort comprised 1276 patients. After introduction of the LAS, the annual number of transplantations and waiting list mortality did not change. The proportion of patients on the waiting list and transplanted patients with pulmonary fibrosis increased (25%–37%, P < 0.001; 22%–39%, P < 0.001). The chance of transplantation increased significantly for patients with pulmonary fibrosis after introduction of the LAS (hazard ratio 1.9 [95% confidence interval 1.4-2.9]). Patients who died on the waiting list had an increased LAS compared to the time of placement on the waiting list, reflecting clinical deterioration. This was not the case in patients with chronic obstructive pulmonary disease ( P < 0.001). Overall survival was similar after introduction of the LAS (5-y survival 68%, compared to 74% [ P = 0.171]). Conclusions: After the introduction of the LAS in The Netherlands, an increased proportion of transplantations was performed for patients with pulmonary fibrosis. Overall survival after transplantation did not change.